2014
DOI: 10.1002/lary.24949
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for otolaryngologists in the multidisciplinary difficult airway response team

Abstract: Otolaryngologists were able to decrease the need for cricothyrotomies using specialized techniques for patients with difficult airways. Otolaryngologists bring a special skill set to the DART that is beyond the scope of anesthesiologists and trauma surgeons and that can improve patient outcomes by preventing unnecessary emergency surgical airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 18 publications
1
56
0
Order By: Relevance
“…This situation can arise independent of location (pre-or in-hospital setting), [1][2][3] clinical expertise (medical technician, nurse, or physician), 4,5 or specialty (emergency medicine, anesthesiology, critical care medicine, or surgery). [6][7][8] The most recent American Society of Anesthesiologists' (ASA) "Practice Guidelines for Management of the Difficult Airway" designate surgical or percutaneous airway, jet ventilation, or retrograde intubation as invasive airway access procedures to secure the airway in both non-emergency and emergency situations. 9 Each of these techniques is usually performed at the cricothyroid membrane (CTM).…”
Section: Résumémentioning
confidence: 99%
“…This situation can arise independent of location (pre-or in-hospital setting), [1][2][3] clinical expertise (medical technician, nurse, or physician), 4,5 or specialty (emergency medicine, anesthesiology, critical care medicine, or surgery). [6][7][8] The most recent American Society of Anesthesiologists' (ASA) "Practice Guidelines for Management of the Difficult Airway" designate surgical or percutaneous airway, jet ventilation, or retrograde intubation as invasive airway access procedures to secure the airway in both non-emergency and emergency situations. 9 Each of these techniques is usually performed at the cricothyroid membrane (CTM).…”
Section: Résumémentioning
confidence: 99%
“…These factors include a history of a difficult airway, cervical spine injury or fixation, oropharyngeal and/or supraglottic angioedema, and airway bleeding. A retrospective review of the first 2 years of the DART program and comparison with a non-DART cohort by Hillel and colleagues 29 showed that oropharyngeal and/or supraglottic angioedema patients were 9 times more likely to require a visit to the operating room for management of their difficult airway compared with patients who did not have angioedema. Identification of a patient with a history of a known difficulty airway is frequently done via an alert on the patient's electronic medical record.…”
Section: Factors Associated With Dart Activationmentioning
confidence: 98%
“…The interaction between multiple specialties builds familiarity and trust that carries over when responding to a difficult airway event in the hospital. 29 It is known that effective teamwork, communication, and coordination among health care providers can aid in preventing adverse patient outcomes. 30 As a result, in recent years there has been a new hospital focus on the multidisciplinary approach to the difficult airway patient.…”
Section: Multidisciplinary Teammentioning
confidence: 99%
See 2 more Smart Citations